INTERVINING DEBT POLICY THE EFFECT FREE CASH FLOW AND INVESTMENT OPPORTUNITY SET TO DIVIDEND POLICY - Sugiyanto Sugiyanto; Rachmat Kartolo; Ali Maddinsyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to examine the effect of free cash flow and investment opportunity set on dividend policy with debt policy as an intervening variable. This type of research is quantitative causality using the population in this study is a consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The selection of data samples using purposive sampling technique. The analytical method used is path analysis. The results of this study indicate that free cash flow has a positive and significant effect on debt policy, investment opportunity set has no effect on debt policy, free cash flow has a positive and significant effect on dividend policy, investment opportunity set has no effect on dividend policy, free cash flow and investment The opportunity set simultaneously influences the dividend policy, the debt policy does not mediate the effect of free cash flow on the dividend policy and the debt policy does not mediate the effect of the investment opportunity set on the dividend policy.